2015
DOI: 10.1002/2015ja021702
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric and geomagnetic responses to interplanetary coronal mass ejections observed by ACE and GRACE: Statistical results

Abstract: For the period July 2003 to August 2010, the interplanetary coronal mass ejection (ICME) catalogue maintained by Richardson and Cane lists 106 Earth‐directed events, which have been measured in situ by plasma and field instruments on board the ACE satellite. We present a statistical investigation of the Earth's thermospheric neutral density response by means of accelerometer measurements collected by the Gravity Recovery And Climate Experiment (GRACE) satellites, which are available for 104 ICMEs in the data s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 60 publications
6
55
0
2
Order By: Relevance
“…For example, CHAMP observations have shown significant changes in response of atmospheric densities to ICMEs (Forbes et al 2005). Recently, Krauss et al (2015) made a statistical analysis of the thermospheric neutral density content during ICME impacts. The authors found significant density enhancements, up to a factor of eight, as a response to ICMEs and a strong correlation with the magnitude of the enhancement and the magnitude of the southward magnetic field in the ICME.…”
Section: Icmes/sheaths As Drivers Of Atmospheric Effectsmentioning
confidence: 99%
“…For example, CHAMP observations have shown significant changes in response of atmospheric densities to ICMEs (Forbes et al 2005). Recently, Krauss et al (2015) made a statistical analysis of the thermospheric neutral density content during ICME impacts. The authors found significant density enhancements, up to a factor of eight, as a response to ICMEs and a strong correlation with the magnitude of the enhancement and the magnitude of the southward magnetic field in the ICME.…”
Section: Icmes/sheaths As Drivers Of Atmospheric Effectsmentioning
confidence: 99%
“…plo, os efeitos causados por interações de estruturas magnéticas de CMEs com a magnetosfera (início da fase principal de tempestade) são mais intensos do que os efeitos causados pelo impacto de CMEs com a magnetosfera (compressão) [51,52].…”
Section: A Termosfera Durante Tempestades Geomagnéticasunclassified
“…Por exemplo, como mostra a equação (1), a densidade de partículas neutraś e proporcionalà aceleração de arrasto do satélite. Utilizando equações para o eixo maior de trajetórias elípticas de satélitesé possível se estimar suas acelerações de arrasto e seu decaimento orbital através da densidade de partículas neutras [52]. Fig.…”
Section: Efeitos Da Tempestade Geomagnéticaunclassified
“…Together with their embedded magnetic field (magnetized plasma clouds) and shocks ahead, CMEs propagate into interplanetary (IP) space with velocities of a few hundred to a few thousand km/s (e.g., Yashiro et al 2004) and may cause severe space weather effects when interacting with the Earth's magnetic field (see e.g., Pulkkinen 2007;Schwenn 2006, and references therein). Even thermospheric responses in terms of a neutral density increase are observed due to CME-Earth interactions (e.g., Guo et al 2010;Krauss et al 2015). The transit times to reach a distance of 1 AU is of about one to five days, and depends on the CME's initial velocity, size, and mass, as well as on the Corresponding author: manuela.temmer@uni-graz.at conditions of the ambient solar wind flow in IP space (see e.g., Bothmer & Daglis 2007).…”
Section: Introductionmentioning
confidence: 99%